Kinetic Control of Block Copolymer Self‐Assembly in a Micromixing Device – Mechanistical Insight into Vesicle Formation Process. Issue 2 (7th November 2016) - Thiermann, Raphael; Bleul, Regina; Maskos, Michael
Abstract : Control over the self‐assembly process plays a crucial role in the synthesis of supramolecular structures. In this study, the formation of block copolymer vesicles from poly(butadiene)‐ block ‐poly(ethyleneoxide) is extensively investigated and analyzed. It is shown how the application of micromixer technology enables not only to control the aggregate size but also to allow trapping thermodynamic instable intermediates during the vesicle formation. Anisotropic disk‐like polymer aggregates are identified by cryo‐TEM (transmission electron microscopy) measurements by tilting the TEM sample holder. These disk‐like micelles represent the precursors of vesicles that form the final spherical hollow spheres by closing up. These intermediates help to gain valuable insight into the self‐assembly mechanism, which is of great importance, e.g., for the successful encapsulation of hydrophilic particles and molecules into vesicular structures for targeted drug delivery. Kinetic control during self‐assembly of amphiphiles in the micromixer device also accomplishes access to highly defined polymer aggregate structures of distinct size and morphology. Abstract : The application of micromixer technology enables kinetic control during self‐assembly of amphiphiles. Thermodynamic instable intermediates can be trapped and highly defined polymer aggregate structures of distinct size and morphology become accessible.